The Effect of Psychoeducational Stress Management Interventions on Students Stress Reduction: Systematic Review - Talal Hassan Bani Ahmad; Meltem Meric; Mohammad Ayasrah (LED Edizioni Universitarie, 2022)
Students can be a vulnerable group for stress. A psycho-educational program is one of the strategies to facilitate students' adjustment and manage stress. This systematic review will integrate the effects of psychoeducational interventions on the level of stress among students. Pubmed, CINAHL, Science Direct Scopus databases were used to find potentially relevant published articles. The title and abstracts are used firstly to screen studies using inclusion and exclusion criteria before going to the next stage of the reviewing of complete articles. A total of eleven articles were selected based on inclusion and exclusion criteria. All articles in this sample were assessed using an instrument to assess overall quality. Study setting, sample size, study interventions, outcome measure/methods of delivery, and results were assessed and extracted. In all of the studies reviewed, the intervention groups experienced significantly greater reductions in perceived stress and symptoms of anxiety and depression. Our review highlights the importance of stress management programs, and the findings from this systematic review indicated that these programs were generally effective for optimizing the stress process and improving coping capacity with stressors.